ТАЛАБАЛАРДА ИЖТИМОИЙ ФАОЛЛИКНИ ШАКЛЛАНТИРИШНИНГ МОҲИЯТИ ВА ФУНКЦИЯЛАРИ - Раҳманова, М.Қ. (SCIENCE and SOCIETY, 2016)
The article contains the characterization of the basis and functions of preparing students social activities of students in the system of higher pedagogical education, there were distinguished aspects of students‘ preparation to social activity.